Efficacy of holmium laser versus pneumatic lithotripsy for mid and distal ureteric stones above 10 mm size - Arvind Arvind; Shiva Manohar Dutta; Sudipta Kumar Singh; Partha Protim Mondal; Shashi Kant Tewary; Ankit Agarwal; Apurv Shukla; Ranjan Kumar Dey; Shiva Manohar Dutta (Asian Journal of Medical Sciences, 2025)
Background: Over the past decade, ureteral stone treatment has evolved significantly. Pneumatic lithotripsy is common but prone to stone migration. Holmium laser use has increased due to fewer complications and lower stone migration rates. Aims and Objectives: The purpose of the study was to compare Lithoclast with holmium: YAG laser lithotripsy for mid and lower ureteral stone and evaluate the complication rate of both for the endoscopic management of ureteric stone. Materials and Methods: This 2-year comparative study at R.G. Kar Medical College and Hospital involved 200 patients with ureteric stones ≥10 mm. Patients were randomized to groups and recorded metrics included duration, complications, and post-procedural ureteroscopic evaluations. Data were analyzed using Microsoft Excel, SPSS (v27.0), and GraphPad Prism (v5), employing two-sample and paired t-tests (significance at P≤0.05). Results: Most participants were aged 21–50 years; the association between Hematuria in immediate post-operative period was significantly more common with Lithoclast (91%) than Laser treatment (69%) (P=0.0001). Submucosal hematoma occurred significantly more with Lithoclast (18%) than Laser treatment (2%) (P=0.0001). Ureteric perforation was significantly more common with Lithoclast than with Laser treatment (P=0.007). At 14 days postoperatively, 8% of the Lithoclast group had residual stones, while the Laser group had a 100% stone-free rate (P=0.0038). Conclusions: This study highlights the comparative efficacy of laser and pneumatic lithotripsy for ureteric stones showing similar outcomes in demographics, stone characteristics, and operative duration. However, the laser group had a higher stone-free rate, fewer complications such as hematuria and ureteric perforation, and fewer residual stones, supporting its growing preference.